Effects of endodontic tri-antibiotic paste on bond strengths of dentin adhesives to coronal dentin - Parvin Mirzakoucheki; Ricardo Walter; Navid Khalighinejad; Maryam Zare Jahromi; Sanaz Mirsattari; Navid Akbarzadeh (Korean Academy of Conservative Dentistry, 2015)
Objectives The aim of this study was to evaluate the effects of tri-antibiotic paste (TAP) on microtensile bond strengths (MTBS) of dental adhesives to dentin. Materials and Methods Sixty extracted molars had their occlusal surfaces flattened to expose dentin. They were divided into two groups, i.e., control group with no dentin treatment and experimental group with dentin treatment with TAP. After 10 days, specimens were bonded using self-etch (Filtek P90 adhesive) or etch-and-rinse (Adper Single Bond Plus) adhesives and restored with composite resin. Teeth were sectioned into beams, and the specimens were subjected to MTBS test. Data were analyzed using two-way ANOVA and post hoc Tukey tests. Results There was a statistically significant interaction between dentin treatment and adhesive on MTBS to coronal dentin (p = 0.003). Despite a trend towards worse MTBS being noticed in the experimental groups, TAP application showed no significant effect on MTBS (p = 0.064). Conclusions The etch-and-rinse adhesive Adper Single Bond Plus presented higher mean bond strengths than the self-etch adhesive Filtek P90, irrespective of the group. The superior bond performance for Adper Single Bond when compared to Filtek P90 adhesive was confirmed by a fewer number of adhesive failures. The influence of TAP in bond strength is insignificant.